EFFECT OF ZEOLITE ADDITION TO PLANT GROWTH MEDIA ON CANTALOUPE AND WATERMELON PLANTS IN HYDROPONIC SYSTEM - Pangestu, M. Bagus; Suwardi, Suwardi; Widiatmaka, Widiatmaka (Jurnal Zeolit Indonesia, 2004)
The objectives of this research are to evaluate the effect of zeolite addition on watermelon and cantaloupe production and growing. The research carried out in green house of Bogor Agricultural University and the plant growth media (PGM) analysis carried out at Department of Soil Science, Faculty of Agriculture, Bogor Agricultural University. Single factor completely randomize design was used with four treatments and five repetitions. Plant growth media composition treatments effect the physical and chemical properties of PGM. The bulk density of PGM increase from from 0.22 to 0.56 g/cm3 and water holding capacity drop from 326.58 to 85.38 along with zeolite percentages added. The effects of zeolite on chemical characteristic of PGM is decreasing electrical conductivity rate before planting. PGM composition treatment did not positively effects on watermelon and cantaloupe growth, however there is an increasing on main stalk length and leaf quantity on cantaloupe. For watermelon, the increasing of growth parameter happened on 10% zeolite percentage. For fruit quality, PGM treatment positively effects on organoleptic test result 10% of zeolite giving the best result on the increasing of the average value of production and growth parameter.